Patients' and caregivers' perspectives of the atopic dermatitis journey - Steven R. Feldman; Alson Wai Ming Chan; Alfred Ammoury; Jianzhong Zhang; Akio Tanaka; XingXiang Shi; Amy Cha; Helen Tran (Taylor & Francis Group, 2024)
AbstractBackground Understanding the patient journey is important to optimize care for patients with atopic dermatitis (AD) and overcome challenges in diagnosis and management.Objective To explore patient and caregiver perspectives regarding their experience with AD.Methods Patients and caregivers of patients with AD completed a pre-meeting survey and were invited to join an advisory board meeting in their country (China, Hong Kong, Ireland, Japan and Lebanon) to discuss the survey results. Data were analyzed descriptively.Results The survey included 31 participants (patients and caregivers) from Hong Kong (n = 7), China (n = 7), Ireland (n = 6), Japan (n = 6) and Lebanon (n = 5). The most challenging factors in the AD journey were management of symptoms before a confirmed diagnosis (68%), sudden recurrence of flares or worsening of symptoms (68%) and lifestyle changes (52%). In terms of overall AD management, 35% of participants indicated that AD was managed well, 23% had a clear treatment plan and 19% were generally satisfied with disease management. A collaborative relationship with healthcare professionals was favored.Conclusion A holistic assessment of AD includes understanding patient and caregiver preferences, needs, experiences and disease perceptions. Addressing the identified gaps may improve the management of AD.